Discurso político legislativo e gênero social : um estudo crítico do Projeto de Lei 120/2011 - Effgen, Zirlene (2016)
In this thesis, we analyze the legislative political discourse embodied in the Law Project 120/2011 submitted to the City Council of Vitoria - ES, noting the ideological forms of power and domination that violate the personal right of transvestites and transsexuals to use their social name in schools. If the reading of a text is a discursive practice that results from constant understanding and interpretation processes, inference, assignments of meanings and values, that is, of our cognitive performances, we start from the hypothesis that this project has evidences recognized by textual/discursive and socio-cognitive strategies related to abuse of power relations and social dominance, capable of manipulating the cognitive process of speech receptors, causing them to develop preferred mental models of discrimination and intolerance of social gender. The theoretical framework that supports this research is supported by the Critical Discourse Studies, Van Dijk (1999, 2003, 2004, 2006, 2009, 2012a, 2012b, 2014), in their social cognitive bias. The objective is to analyze, through the ideology of Thompson's Operation Modes (1999) and contributions of sociocognitive proposal, as the discourse is built in the political sphere, to reinforce ideologies and social practices that violate the right to gender identity and how this discourse works with the development and reproduction of discriminatory mental models. As a methodological approach, we adopt the interpretative qualitative research and use ethnographic research as a method for data collection. The results obtained by the analysis allowed us to show that the Law Project 120/2011, although they try to promote democracy ensured by the constitutional procedural law, what has been recognized is a concealment of political and social interests that still try to legitimize dominance relations and power over the relations of social gender.